Ginástica para todos e produção do conhecimento: estado da arte dos artigos publicados em periódicos nacionais no período de 1980 a 2018 - ANDRADE, Welison Alan Gonçalves (2020)
This research aimed to analyze the scientific research on Gymnastics for All (GPT) published in national electronic journals from 1980 to 2018. The study was set up as a state of the art, in which 34 articles published in 12 journals in the period from 1980 to 2018. In the analysis of the data was highlighted the quantity of publications in each year of the selected period, the topics addressed in the investigations, the type of research and the most used theoretical references. The analysis indicates that the Brazilian scenario of publication of articles about GPT is incipient, that 2016 was the year with the highest quantitative publication balance, and most studies have female authors as the first author. Of the analyzed journals, the magazine Conexões was the one that made more publications of articles on the mentioned subject, showing that the majority of the existing production, is characterized by studies directed to the category of the School and are predominantly surveys.